Meningkatkan Visibilitas Perpustakaan Melalui Media Sosial: Studi Kasus di Perpustakaan Universitas Ciputra Makassar - Ramadayanti (Inkunabula: Journal of Library Science and Islamic Information, 2025)
This study examines the enhancement of the visibility of the Ciputra University Makassar Library through the utilisation of social media platforms. The research addresses two principal questions: How is social media leveraged to increase the visibility of the Ciputra University Makassar Library? and How is social media strategically employed by the Library? The purpose of this study is to explore and describe the visibility efforts and the utilisation of social media by the Library. A descriptive qualitative approach, employing a case study design, was adopted to obtain an in-depth understanding of the Library’s social media practices aimed at increasing its visibility. Data were collected from librarians, social media management staff, and students of Ciputra University Makassar. The findings reveal that the use of social media, particularly Instagram and Facebook, has significantly enhanced the visibility of the Ciputra University Makassar Library among students and the wider academic community. Through the dissemination of informative, interactive, and visually appealing content, the Library has successfully fostered closer communication with its users and promoted a range of services, including Turnitin support, a One Stop Service, access to the online book collection, reading recommendations, and information literacy classes. Despite ongoing challenges regarding content consistency and the diversification of communication strategies, social media has proven to be an effective medium for reinforcing the Library’s role as a dynamic centre for information dissemination and digital literacy development. Abstrak Penelitian ini berfokus tentang Meningkatkan Visibilitas Perpustakaan Universitas Ciputra Makassar Melalui Media Sosial. Rumusan masalah pada penelitian ini adalah; Bagaimana visibilitas media sosial oleh perpustakaan Universitas Ciputra Makassar? dan Bagaimana pemanfaatan media sosial oleh perpustakaan Universitas Ciputra Makassar? sementara tujuan penelitian ini adalah untuk menguraikan visbilitas dan pemanfaatan media sosial oleh Perpustakaan Universitas Ciputra Makassar. Penelitian ini menggunakan pendekatan kualitatif deskriptif dengan desain studi kasus untuk memahami secara mendalam pemanfaatan media sosial oleh Perpustakaan Universitas Ciputra Makassar dalam meningkatkan visibilitasnya. Sumber data berasal dari pustakawan, staf pengelola media sosial, serta mahasiswa Universitas Ciputra Makassar. Kesimpulan dari hasil penelitian menunjukkan bahwa visibilitas media sosial, khususnya Instagram dan Facebook, secara signifikan meningkatkan visibilitas Perpustakaan Universitas Ciputra Makassar di kalangan mahasiswa dan sivitas akademika. Melalui konten yang informatif, interaktif, dan visual menarik, perpustakaan berhasil membangun komunikasi yang lebih dekat dengan pengguna serta memperkenalkan berbagai layanan seperti Turnitin, One Stop Service, penelusuran koleksi buku, rekomendasi bacaan, dan kelas literasi informasi. Meskipun masih terdapat tantangan dalam hal konsistensi konten dan variasi strategi komunikasi, media sosial telah terbukti menjadi sarana efektif dalam memperkuat peran perpustakaan sebagai pusat informasi dan literasi digital yang relevan.